2017
DOI: 10.1098/rsif.2016.0846
|View full text |Cite
|
Sign up to set email alerts
|

Deep conservation of bivalve nacre proteins highlighted by shell matrix proteomics of the Unionoida Elliptio complanata and Villosa lienosa

Abstract: The formation of the molluscan shell nacre is regulated to a large extent by a matrix of extracellular macromolecules that are secreted by the shell-forming tissue, the mantle. This so-called ‘calcifying matrix’ is a complex mixture of proteins, glycoproteins and polysaccharides that is assembled and occluded within the mineral phase during the calcification process. Better molecular-level characterization of the substances that regulate nacre formation is still required. Notable advances in expressed tag sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 70 publications
(137 reference statements)
2
71
1
Order By: Relevance
“…The organic matrix guarantees mineral and macromolecule interactions as it has a main role in crystal nucleation and growth [10]. The mechanism of nacre formation has been studied through extraction and functional studies of various shell matrix proteins (SMPs); nevertheless, nacre biomineralization is a very complex process; thus, soluble and insoluble proteins in ethylenediaminetetraacetic acid (EDTA) or 10% acetic acid have been studied because of their biochemical and crystallization nacre properties [11,12]. Previous studies have reported that peptide sequences from insoluble and soluble matrixes share conserved regions or domains; however, shell matrix protein sequences are generally dominated by Asp, Glu, Ser, Ala, Gly, Pro and Cys residues, which are often concentrated in short or long repetitive domains [5,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The organic matrix guarantees mineral and macromolecule interactions as it has a main role in crystal nucleation and growth [10]. The mechanism of nacre formation has been studied through extraction and functional studies of various shell matrix proteins (SMPs); nevertheless, nacre biomineralization is a very complex process; thus, soluble and insoluble proteins in ethylenediaminetetraacetic acid (EDTA) or 10% acetic acid have been studied because of their biochemical and crystallization nacre properties [11,12]. Previous studies have reported that peptide sequences from insoluble and soluble matrixes share conserved regions or domains; however, shell matrix protein sequences are generally dominated by Asp, Glu, Ser, Ala, Gly, Pro and Cys residues, which are often concentrated in short or long repetitive domains [5,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In bivalves, more than 50 different insoluble proteins have been described; some of them are N14/N16/pearlin family, Pif-like family, UNP-family, MSI60-like family, Fam20c, N25, Prismalin-14 [2,3,11,16,18,[21][22][23][24][25][26]. Insoluble acetic acid proteins, such as Pif, MSI60, proteins containing a carbonic anhydrase domain (CA), proteins with LamG (a Ca +2 mediated receptor), chitin-binding-containing proteins, together with A-, D-, G, M-and Q-rich proteins, appear to be analogs of proteins previously described from pearl oysters or edible mussel nacre matrices, which constitutes a remarkable set of deeply conserved nacre proteins [11,27]. A proteomic analysis of the insoluble acetic-acid nacre matrices of fresh water mussels showed different domains according to their protein sequences, such as RLCD-(repetitive low-complexity domain), immunity-related, Pif-, WAP-, M-rich, Q-rich, A-rich or chitin binding [11,12,28].…”
Section: Introductionmentioning
confidence: 99%
“…As one type of PDCP, WLP has 147 residues, of which Gln is the most abundant amino acid (9.5%) in its sequence, followed by Gly (8.8%) and Arg (8.2%) (S2 Table). SMPs rich in Gln have been found in various Mollusca shells, such as those of Pinctada margaritifera [33], the gastropod Lottia [34], Unionidae Elliptio complanata, and Villosa lienosa [35]. Interestingly, vertebrate teeth also contain Gln-…”
Section: Discussionmentioning
confidence: 99%
“…A nacre protein was also altered in mussels exposed to M. aeruginosa. Nacre proteins are constituents of the shell matrix of bivalves, and among the functions attributed to these proteins is shell calcification [47,48]. Moreover, STRING analysis highlighted the putative role of CALR and YWHAE in mediating the molecular response in mussels, as these proteins seemed to be functionally related with several differentially expressed proteins and showed to be central elements of the protein networks reported (Figure 7a).…”
Section: Metabolic Responses Of Mussels To Toxic Cyanobacteriamentioning
confidence: 94%